THE ROLE OF TRAINING IN IMPROVING EMPLOYEE PERFORMANCE: A SURVEY OF A SAMPLE OF EMPLOYEES AT UNIVERSITY OF MAYSAN (World Bulletin of Social Sciences, 2023)
This study dealt with analysis of relationship and impact between training and improving performance of workers, which has become a vital and contemporary topics as interest in training has increased in present, and study provided a theoretical briefing on training and improving performance of workers. As for practical framework of study, an educational sector, University of Maysan, was selected as an area to conduct field side of study, where (100) was distributed to a group of administrative leaders at University of Maysan and its colleges, and after tabulation of data showed that number of valid questionnaires reached (78) a questionnaire, questionnaire was used as a main tool for collecting data from staff members of faculties of research university. Study focused on role of application of training in improving performance of employees at University of Maysan and adopted a set of main and subhypotheses to solve this problem, and in order to achieve objectives of study and its hypotheses was formulated a hypothetical model that explains nature of relationship and impact between variables of study. Study concluded with a set of conclusions and recommendations reached through results of field study, most important of which is existence of a moral link between internal marketing procedures and performance of employees. At level of subvariables, relationship between procedure of disseminating marketing information to employees in performance of workers is not moral. researcher reached through practical side of research for independent variable according to arithmetic mean that (Maysan University and its colleges) is primarily interested in modern technology, followed by an interest in design of training process.